Histamine Polarizes Human Dendritic Cells into Th2 Cell-Promoting Effector Dendritic Cells - Caron, Gersende; Delneste, Yves; Roelandts, Edith; Duez, Catherine; Bonnefoy, Jean-Yves; Pestel, Joel; Jeannin, Pascale (The Journal of immunology (1950), 2001)
Allergic disorders are characterized by allergen-specific Th2-biased responses. Signals controlling Th2 cell polarization, especially those acting by polarizing dendritic cells (DC) into Th2-promoting DC (DC2), are not well known. Histamine, a mediator released by allergen-stimulated mast cells from allergic subjects, has been reported to activate human immature DC. We have therefore tested whether histamine affects DC polarization. We report here that histamine inhibits LPS-induced IL-12 production and polarizes uncommitted maturing DC into effector DC2. DC matured in the presence of histamine fail to produce IL-12 upon subsequent stimulation and prime Th2 responses, even in presence of IFN-γ, a potent DC1-driving factor. All these effects are mediated through both H1 and H2 receptors. These data show that histamine is a potent DC2-polarizing factor and provide evidence for a novel mechanism that explains the initiation and maintenance of a predominant Th2 response in allergic disorders.